2023
DOI: 10.1111/cbdd.14237
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 integrase inhibitor raltegravir promotes DNA damage‐induced apoptosis in multiple myeloma

Abstract: Raltegravir, the first integrase inhibitor approved for the treatment of HIV infection, has been implicated as a promising potential in cancer treatment. Therefore, the present study aimed to investigate the repurposing of raltegravir as an anticancer agent and its mechanism of action in multiple myeloma (MM). Human MM cell lines (RPMI‐8226, NCI H929, and U266) and normal peripheral blood mononuclear cells (PBMCs) were cultured with different concentrations of raltegravir for 48 and 72 h. Cell viability and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…The induction of ferroptosis has been suggested to arise from either DNA damage or the release of reactive oxygen species [3,71]. As previously reported [72], raltegravir, an integrase inhibitor, was able to induce regulated cell death in multiple myeloma by damaging DNA. Consequently, cabotegravir induce apoptosis and/or ferroptosis in melanoma cell lines, causing DNA damage.…”
Section: Discussionmentioning
confidence: 60%
“…The induction of ferroptosis has been suggested to arise from either DNA damage or the release of reactive oxygen species [3,71]. As previously reported [72], raltegravir, an integrase inhibitor, was able to induce regulated cell death in multiple myeloma by damaging DNA. Consequently, cabotegravir induce apoptosis and/or ferroptosis in melanoma cell lines, causing DNA damage.…”
Section: Discussionmentioning
confidence: 60%
“…As the first integrase inhibitor approved for the treatment of HIV infection, Raltegravir is gradually being discovered to have effects other than anti-HIV. Studies have shown that Raltegravir may be effective in treating multiple myeloma by promoting DNA damage-induced apoptosis [ 49 ]. Another study showed that Raltegravir was effective in treating human T-cell lymphoblastic virus-1 (HTLV-1)-associated myelopathy/tropical spastic paraplegia (HAM/TSP).…”
Section: Discussionmentioning
confidence: 99%